2009
DOI: 10.1152/ajpregu.90363.2008
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 and A2a receptors modulate insulinemia, glycemia, and lactatemia in fetal sheep

Abstract: A 1 and A2A receptor subtypes modulate metabolism in adult mammals. This study was designed to determine the role of these receptors in regulating plasma levels of insulin, glucose, and lactate in 20 chronically catheterized fetal sheep (Ͼ0.8 term). In normoxic fetuses (Pa O 2 ϳ24 Torr), systemic blockade of A1 receptors with DPCPX (n ϭ 6) increased plasma concentrations of insulin, glucose, and lactate, but antagonism of A 2A receptors with ZM-241385 (n ϭ 5) had no significant effects. Intravascular administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 51 publications
1
12
0
2
Order By: Relevance
“…However, we noticed that hypoxia increased the anaerobic glycolysis in CEM cells by significantly increasing the lactate production in the culture medium at 9 and 12 h. This is in agreement with previous observations that, after stimulation, the glucose catabolism in immune cells increased [16] and that inhibitors of glycolysis impaired the function of immune cells whereas inhibitors of oxidative phosphorylation did not [17][18][19]. Our results also fit nicely with a recent report that concludes to a role of hypoxiainduced adenosine via A 2A R in high glucose and lactate plasma levels [20].…”
Section: In Vitro Hypoxia Conditionssupporting
confidence: 93%
“…However, we noticed that hypoxia increased the anaerobic glycolysis in CEM cells by significantly increasing the lactate production in the culture medium at 9 and 12 h. This is in agreement with previous observations that, after stimulation, the glucose catabolism in immune cells increased [16] and that inhibitors of glycolysis impaired the function of immune cells whereas inhibitors of oxidative phosphorylation did not [17][18][19]. Our results also fit nicely with a recent report that concludes to a role of hypoxiainduced adenosine via A 2A R in high glucose and lactate plasma levels [20].…”
Section: In Vitro Hypoxia Conditionssupporting
confidence: 93%
“…Adenosine can regulate inflammation 68 , as well as metabolic processes involved in insulin homeostasis 910 , glucose metabolism 1113 , lipolysis 1415 and cholesterol synthesis 16 . Of all four adenosine receptors, the A 2b AR has the lowest affinity for adenosine 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The null mice showed also an enhanced second phase of pancreatic insulin secretion (Johansson et al, 2007a). A recent study by Maeda and Koos (2008), suggested that in adult animals endogenous adenosine reduces plasma concentrations of insulin, glucose, and lactate via the selectively inhibiting A 1 AR. These studies demonstrate that in vivo elimination or inhibition of A1AR has an effect on glucose homeostasis and the effect is contingent upon the length of the diet or the level of obesity.…”
Section: Adenosine and A1 Adenosine Receptorsmentioning
confidence: 99%
“…Studies have shown that exogenous adenosine signaling through A 2a AR increases gluconeogenesis and glucose release (González‐Benítez et al, 2002; Yasuda et al, 2003; Maeda and Koos, 2008). In fetal sheep, A 2a AR activation increases glucose and lactate levels as a result of the increased endogenous adenosine levels under hypoxic conditions (Table 4; Maeda and Koos, 2008). In rat hepatocytes, gluconeogenesis stimulation was also observed by the activation of A 2a AR with a selective agonist (CGS‐21680) in cAMP‐dependent manner (González‐Benítez et al, 2002).…”
Section: A2a Adenosine Receptorsmentioning
confidence: 99%
See 1 more Smart Citation